Research on the Impact of PAD Class on Junior High School Students' English Learning Motivation and Autonomous Learning Ability - Xie, Yanhong; He, Piaoxue (Journal of Educational Research and Policies, 2025)
Motivation and autonomous learning ability are widely recognized as two pivotal factors influencing learners’ success. However, in many contexts of Chinese middle school English teaching, current pedagogical practices often fail to adequately foster them. As an emerging teaching model, PAD Class offers a promising framework for addressing this issue. This study, taking 59 Chinese junior high school students as research sample, explores the impact of PAD Class on junior high school students' English learning motivation and autonomous learning ability. By employing multiple research methods and instruments including experiment, questionnaire, observation and SPSSAU, it is found that PAD Class can significantly improve students’ learning motivation and enhance their autonomous learning ability and awareness. Then, some suggestions are proposed for better leveraging the advantages of PAD Class in junior high school English instruction and further research. This study provides practical guidance for the reform of junior high school English teaching, helps students achieve all-round development, and offers a reference for the research on the innovation of teaching models.